Monitoring polymerization reactions : from fundamentals to applications - Reed, Wayne F.; Alb, Alina M. (John Wiley & Sons, Inc., 2014)
With contributions from leading macromolecular scientists and engineers, this book provides a practical guide to polymerization monitoring. It enables laboratory researchers to optimize polymer reactions by providing them with a better understanding of the underlying reaction kinetics and mechanisms. Moreover, it opens the door to improved industrial-scale reactions, including enhanced product quality and reduced harmful emissions. As new stimuli-responsive and "intelligent" polymers continue to be developed, the ability to monitor reactions will become increasingly important. With this book as their guide, polymer scientists and engineers can take full advantage of the latest monitoring strategies to optimize reactions in both the lab and the manufacturing plant. - Resumé vydavatel
Includes index.
Keywords: polymerizace; chemické reakce; polymerization; chemical reactions; elektronické knihy; sborníky; electronic books; papers of several authors